Achieving High Efficiency and Improved Stability in ITO‐Free Transparent Organic Light‐Emitting Diodes with Conductive Polymer Electrodes. (26th February 2013) - Kim, Yong Hyun; Lee, Jonghee; Hofmann, Simone; Gather, Malte C.; Müller‐Meskamp, Lars; Leo, Karl
Abstract Efficient transparent organic light‐emitting diodes (OLEDs) with improved stability based on conductive, transparent poly(3, 4‐ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) electrodes are reported. Based on optical simulations, the device structures are carefully optimized by tuning the thickness of doped transport layers and electrodes. As a result, the performance of PEDOT:PSS‐based OLEDs reaches that of indium tin oxide (ITO)‐based reference devices. The efficiency and the long‐term stability of PEDOT:PSS‐based OLEDs are significantly improved. The structure engineering demonstrated in this study greatly enhances the overall performances of ITO‐free transparent OLEDs in terms of efficiency, lifetime, and transmittance. These results indicate that PEDOT:PSS‐based OLEDs have a promising future for practical applications in low‐cost and flexible device manufacturing.